PERSEPSI PETANI TERHADAP PERAN PENYULUH PERTANIAN DI DESA LADA MANDALA JAYA KECAMATAN PANGKALAN LADA KABUPATEN KOTAWARINGIN BARAT - M. Amrullah; Abdul Mukti; Eka Nor Taufik (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2019)
This study aims to determine the perception of farmers on the role of agricultural extension. Extension roles/duties include education, dissemination of information/innovation, facilitation, consultation, supervision, monitoring and evaluation, where the sixth in this study into research variables. Likert scale is used to measure the perception of rubber farmers to the overall role of agricultural extension workers. From the results of the research note that the perception of farmers for the role of extension workers in the value is in the category ?enough to play'' with the overall average of 3.11. The perception of farmers on the role of agricultural extension in Lada Mandala Jaya Village, Pangkalan Lada Sub-district can be categorized as (a). ?role? (mean = 3,69) for sub-variable of Education, (b). ?role? (mean = 3,41) for the sub-variable Dissemination, (c). ?lacks role'' (average = 2.24) as the Facilitator, (d). ?enough role? (average = 3.15) as consultant, (e). ?enough role? (average = 2.60) as Supervisor, and (f). ?enough role? (average = 2.61) in the implementation of Monitoring and Evaluation. It is advisable to extension workers to optimize the role of extension workers, especially in facilitating and supervising the farmers in the development of rubber plantation business.